Production of glucose using banana peel powder: optimization studies - Fatimah Ibrahim (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Banana is major cash cropof many regions generating good amount of waste after harvest. Production of glucose from agro waste is the one way to reduce the agro industrial pollution to the environment. The production of sugars evaluated from non edible (peel) portion of banana fruit has considerable potential in the future to achieve economic profits. Enzymatic hydrolysis of banana peels finds potential application in commercial production of glucose. The effect of various process variables were studied for optimum conversion of banana peel to glucose using cellulase. In order to get higher glucose concentration enzymatic hydrolysis must be optimized. Central Composite Design (CCD) was used in the design of experiments and analysis of results. The optimal condition for enzymatic hydrolysis of 35% banana peel with temperature 45.4 c, time is 9.78 hours and 13.58% of enzyme concentration. A model adequacy was very satisfactory; the optimum glucose was produce is 32.1154 g/l with the correlation coefficient value is 0.9463 respectively.